THE USE OF IMMERSIVE SYSTEMS AS AN OBJECT AND MEANS OF LEARNING - Shekerbekova, Ш.Т.; Zhabayev, Е.Х.; Grinshkun, А.Г.; Revshenova, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Virtual computer models open up new opportunities for demonstrating objects, processes or phenomena, while avoiding the previously mentioned limitations. The purpose of the work is to study the issues of modeling the preparation of teachers for the use of immersive systems as an object and means of teaching. The article highlights the potential of immersive technologies such as virtual and augmented reality to improve education and productivity in various fields. Virtual and augmented reality enable the creation of interactive lessons and simulations that make learning more engaging and allow students to become immersed in the learning material. Immersive technologies allow students to practice in realistic scenarios, such as a medical simulation or virtual laboratory, to enhance understanding and retention. Immersive technologies allow people to travel to virtual places and times that are inaccessible to them due to physical limitations or historical reasons. In areas where professional training is required, such as aviation, medicine, engineering and manufacturing, immersive technologies can be used to simulate complex scenarios and training. Immersive technologies can support shared learning and collaboration, even when participants are located at great distances from each other